The WANING of SCIENTIFIC INNOVATION. - MENKE, J. MICHAEL (Skeptic, 2024)
The article critiques the claim in a recent Nature report that scientific innovation has declined by 90 percent since World War II. Topics discussed include the role of specialization versus generalization in fostering innovation, the impact of university structures on research productivity, and the effects of productivity tools like Six Sigma on creativity and innovation.